Pengaruh Penggunaan Metode Pembelajaran Kooperatif Tipe STAD terhadap Keaktifan Belajar dan Hasil Belajar Siswa pada Proses Pembelajaran Al-Qur’an dan Hadits di Kelas XI IPA 2 MAN I Pekanbaru - Rajulaini Rajulaini (Milenial: Journal for Teachers and Learning, 2022)
This research is motivated by the initial survey that the conditions of teaching and learning the Qur'an and hadits in class XI IPA 2 MAN 1 Pekanbaru already using cooperative learning methods, such as jigsaw. However, the low student learning activities, as well as on student learning outcomes is still mediocre. Therefore, this study wanted to test whether there is significant influence implementation of STAD cooperative method to study activity of student learning of the learning process in the al-Quran and Hadits class XI IPA 2 MAN 1 Pekanbaru? And whether there are significant differences STAD cooperative implementation method with conventional methods of student learning outcomes in subjects al-qu'anand Hadits inclass XI IPA 2 MAN 1 Pekanbaru? These results indicate that first, there are significant differences between students' learning activities before and after the learning method STAD cooperative. It is based on the results of t-test value of 24 371 with sig (a one-tailed) 0.000> 0.05. Secondly there is significant influence implementation of STAD cooperative method of student learning outcomes in subjects al-qu'anand hadist in class XI IPA 2 MAN 1 Pekanbaru. This is shown by the results of the t-test value of 12,200 with sig (2-tailed) 0.000 <0.05.